Handling Fuzzy Points and Fuzzy Lines using the FuzzyGeometry Abstract Data Type - Chaves Carniel, Anderson; Rodrigues Ciferri, Ricardo; Dutra de Aguiar Ciferri, Cristina (Journal of Information and Data Management, 2016)
Crisp spatial objects are geometric features with exact location on the extent and well-known boundaries. On the other hand, vague or fuzzy spatial objects are characterized by uncertain or blurred boundaries and interiors. Despite the importance of fuzzy spatial data in spatial applications, few related work indeed implement them. In addition, related work do not define abstract data types to enable the management of fuzzy spatial objects by using database management systems (DBMS). In this article, we propose the abstract data type FuzzyGeometry to handle fuzzy spatial objects in the PostgreSQL DBMS. Its implementation is open source. It offers management for fuzzy point objects and fuzzy line objects as well as provides several operations to handle them. As a result, users are able to access PostgreSQL in order to use fuzzy spatial objects in spatial queries.